Relationships between reduction in symptoms and restoration of function and wellbeing: Outcomes of the Oral Ketamine Trial on Suicidality (OKTOS). (November 2021) - Beaudequin, Denise; Can, Adem T.; Jones, Monique; Yang, Cian; Scherman, Jennifer K.; Dutton, Megan; Schwenn, Paul; Forsyth, Cyrana Gallay Grace; Jensen, Emma; Hermens, Daniel F.; Lagopoulos, Jim
Highlights: Effect size of oral ketamine on functioning and wellbeing was relatively small. Suicidality and depression measures displayed larger effect sizes. Bayesian networks facilitate interactive multivariate examination in psychiatry. Bayesian modelling revealed wellbeing as the ideal treatment endpoint. Reduced depression and suicidality are necessary but not sufficient for recovery. Abstract: Recovery of functioning is integral to successful treatment outcomes in depressive illness. Optimal antidepressant treatment results in both symptomatic remission and functional recovery. Oral ketamine rapidly reduces suicidality and depression; however, reports of functional and wellbeing outcomes are lacking. This study examines participants' social and occupational functioning and wellbeing outcomes in the Oral Ketamine Trial on Suicidality (OKTOS). Thirty adults with chronic suicidality participated in the trial over 10 weeks. Functional recovery and wellbeing were assessed using the Social and Occupational Functioning Scale (SOFAS) and World Health Organization Well-Being Index (WHO-5). Suicidality and depressive symptoms were assessed using the Beck Scale for Suicidal ideation (BSS) and Montgomery-Asberg Depression Rating Scale (MADRS). Relationships between the four treatment outcomes were analysed. Forty-three percent of participants achieved healthy function (SOFAS ≥ 80) and 27% reported healthy wellbeing (WHO-5 > 60%) at the four-week post-treatment follow-up. Wellbeing was revealed as the data-derived treatment endpoint for the sample. Effect sizes for functioning and wellbeing outcomes were smaller than for suicidality and depression outcomes. Results suggest that reduction in depressive symptoms and suicidal ideation may be necessary but not sufficient for full restoration of function and wellbeing in antisuicidal and antidepressant therapy, including clinical trials. Graphical abstract: Image, graphical abstract